Relationship of Stress with Academic Performance among University Students - Zainab Bibi; Dr. Sajid Mahmood Alvi; Zainab Noor (Journal of Management Practices, Humanities and Social Sciences, 2022)
The current study's goal was to investigate the connection between university students' stress levels and their academic achievement. Using a basic random sample procedure, a sample size of 200 people was drawn from the University of Haripur. Data from 100 male and 100 female university students were included in the sample. Student Stress Inventory (SSI), a tool used to gauge stress among college students, was utilized to gather data. The Grade Point Average (GPA) of each student served as a measure of their academic success. The study's results show a strong correlation between stress and university student’s academic performance, and stress is negatively connected with academic performance among university students. In comparison to male pupils, female students performed better on the stress test. Academic success is inversely connected with stress. Because the current study was restricted to the university of Haripur and the sample size was also small, it was recommended that this study be conducted in the future with a more diverse population and a larger sample size. The results of the current study will contribute to a better understanding of how stress affects university students' academic performance.